Cheaper, cleaner power: De-risking as an anti-collusion strategy in Bangladesh - Khan, Mushtaq; Matin, Maria; Zahan, Iffat; Ashraf, Zeeshan; Ajefu, Joseph (ACE SOAS Consortium, 2020)
Includes bibliographical references (pages 37-38)